Investigation on the size and percentage effects of magnesium nanoparticles on thermophysical properties of reinforced calcium phosphate bone cement by molecular dynamic simulation - Mostafa Mahjoory; Mohamad Shahgholi; Arash Karimipour (Heliyon, 2023)
In recent years, bone materials and cement innovation have made extraordinary strides. Calcium phosphate cement (CPC) regenerates body tissues and repairs bone and dental defects. Since the presence of nanoparticles (NPs) increased the initial cement strength in terms of the reduction of porosity, magnesium (Mg) NPs were used because of their unique properties. In this study, the effects of various Mg NP percentages and sizes on reinforced cement thermal behavior and mechanical behavior are investigated using the molecular dynamics (MD) simulation method. The changes of Young's modulus (YM), maximum temperature (MT), and ultimate strength (US) were investigated for this reason. The US, YM, and MT of the reinforced cement sample improved from 0.879 to 0.171 MPa to 1.326 and 0.255 MPa, respectively, and from 1321 to 1403 K by raising the NPs percentage to 4%. The radius increase of NPs to 16 Å enhanced the US, YM, and MT to 0.899 MPa, 0.179 MPa, and 1349 K. The MT decreased to 1275 K. The quantity and size of the Mg NPs significantly enhanced the mechanical behavior of the finished cement, according to the findings.